Allelopathy 2012
DOI: 10.1007/978-3-642-30595-5_17
|View full text |Cite
|
Sign up to set email alerts
|

Microscopy for Modeling of Cell–Cell Allelopathic Interactions

Abstract: The application of various microscopy methods-from stereomicroscopy to luminescence microscopy, microspectrofluorimetry and laser-scanning confocal microscopy-has been considered as an approach to model the cell-cell contacts and interactions in allelopathy. It bases on the direct observations of both secretions released from allelopathic species and the interaction(s) with the cell acceptors as biosensors (unicellular plant generative and vegetative microspores). Special attention was paid to the interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Crystals of secretions emit more brightness than liquids. Today the secretion peaks were compared with the maxima of individual components of the same secretions in solutions or films [5,8,10]. Interference of various fluorophores in total emission may take place, but diagnostics of prevailing component of the secretion is real.…”
Section: Images and The Fluorescence Spectra Of Fluorescing Cells In mentioning
confidence: 99%
See 1 more Smart Citation
“…Crystals of secretions emit more brightness than liquids. Today the secretion peaks were compared with the maxima of individual components of the same secretions in solutions or films [5,8,10]. Interference of various fluorophores in total emission may take place, but diagnostics of prevailing component of the secretion is real.…”
Section: Images and The Fluorescence Spectra Of Fluorescing Cells In mentioning
confidence: 99%
“…450 nm), and flavins (max. 520 nm) [3], although in dry state weak blue fluorescence (420-450 nm) is also peculiar to isolated nucleotides, RNA, and DNA as well as some proteins, and seen in the films under luminescence microscope [4,5], but water quenches the emission [4]. Besides, there are characteristic fluorescent compounds in various organisms [6].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies demonstrated that these allelopathic effects were caused by the chemicals secreted from some ligneous plants (tree or bushes) (Chaves and Escudero 1997;Kocaçalışkan and Terzi 2001;Boz et al, 2003;Djurdjvic et al, 2005;Ercişli et al, 2005;Bulut and Demir 2007;Roshchina et al, 2011). Similarly, it was observed that ryegrass under Scots pine trees in Erzurum (eastern Turkey) had a weak development.…”
Section: Introductionmentioning
confidence: 97%
“…Pseuduridine modification helps stabilize RNA structure and ribosome biogenesis and activity and regulates rRNA processing, pre-mRNA splicing, and protein synthesis, thereby controlling growth, development, and response to stress in different organisms ( Lu et al., 2017 ; Adachi et al., 2019 ; Sun et al., 2019 ; Wang et al., 2022 ). Ferulic acid and other phenolic acids have an inhibitory effect on plant growth, which can inhibit plant nutrient absorption, photosynthesis, respiration, the function and activity of various enzymes, endogenous hormone synthesis, and protein synthesis ( Hussain and Reigosa, 2021 ; John and Sarada, 2012 ).…”
Section: Discussionmentioning
confidence: 99%